2017
DOI: 10.1186/s12935-017-0491-x
|View full text |Cite
|
Sign up to set email alerts
|

Hedgehog/Gli1 signaling pathway regulates MGMT expression and chemoresistance to temozolomide in human glioblastoma

Abstract: BackgroundChemoresistance of glioblastoma (GBM) is a feature of this devastating disease. This study is to determine the relationship between Hedgehog (HH)/Gli1 signaling pathway and chemoresistance to temozolomide (TMZ) in human GBM.MethodsWe analyzed Gli1 nuclear staining and O6-methylguanine DNA methyltransferase (MGMT) expression in 48 cases of primary GBM tissues by immunohistochemistry. Quantitative PCR, western blot, methylation-specific PCR, cell proliferation and apoptosis assay were used to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 33 publications
3
41
0
Order By: Relevance
“…Thus, in 'exchange condition', the GBM cells were first submitted to cyclopamine followed by TMZ treatment (Cyclo/TMZ) or vice-versa (TMZ/Cyclo). In all combined treatment conditions, we observed a significant decrease in cell viability, as described in previous studies [25,42]. The pharmacological combination of TMZ and cyclopamine (TMZ+Cyclo) showed a cooperative effect, corroborating the idea that the pharmacological combination of TMZ with other drugs, such as SHH inhibitor GANT61, are more successful than monotherapy by decreasing the cell viability of GBM cells [1,[60][61][62].…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Thus, in 'exchange condition', the GBM cells were first submitted to cyclopamine followed by TMZ treatment (Cyclo/TMZ) or vice-versa (TMZ/Cyclo). In all combined treatment conditions, we observed a significant decrease in cell viability, as described in previous studies [25,42]. The pharmacological combination of TMZ and cyclopamine (TMZ+Cyclo) showed a cooperative effect, corroborating the idea that the pharmacological combination of TMZ with other drugs, such as SHH inhibitor GANT61, are more successful than monotherapy by decreasing the cell viability of GBM cells [1,[60][61][62].…”
Section: Discussionsupporting
confidence: 87%
“…As expected, a significant viability reduction in all GBM cell lines treated with 200μM TMZ for 144 hours was observed (6 days-time relatively similar to chemotherapy treatment) [56]. Previous reports have demonstrated the effectiveness of the combination of higher concentrations of TMZ with other compounds, such as cyclopamine in GBM cells [25,57]. However, the need to use lower concentrations of TMZ associated with other compounds to better reduce the side effects as compared to TMZ monotherapy has been exploited [27,58,59].…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…Recent publications indicated that deregulated developmental pathways play a key role in GBM progression and tumorigenesis by conferring drug resistance to the tumor cells and that inhibition of Hedgehog pathway induced apoptosis in GBM cells 16-18 . We had previously demonstrated that Compound #5 activates the Hedgehog pathway through binding to the transmembrane domain of Smoothened 7 .…”
Section: Introductionmentioning
confidence: 99%